The Effect Of Location And Service Quality On Customer Loyalty At Brilink Agent Kembar Sepasang Dusun II Penarik Mukomuko Regency - Purwasi, Ira; Anggriani, Ida; Febliansah, Muhammad Rahman (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2025)
The role of strong access to financial services will be able to maintain the stability and economic growth of each individual, both from the upper middle class and from the underprivileged segments of society. So when all levels of society have equal access to financial services and according to their needs, it indirectly helps strengthen the country's overall economic foundation. This condition makes BRILink agents the spearhead in ensuring that financial services are not only limited to big cities, but also penetrate into remote villages. Meanwhile, the purpose of this study was to determine the effect of location and service quality on customer loyalty at BRILink Agent Kembar Sepasang Dusun II Penarik, Muko-Muko Regency.This research is included in explanatory research with a quantitative approach, which uses multiple linear regression analysis methods. The role of strong access to financial services will be able to maintain the stability and economic growth of each individual, both from the middle to upper class and from the lower segments of society. Meanwhile, the population in this study are people who are customers or users of financial services at BRILink Kembar Sepasang Agent Dusun II Penarik, Muko-Muko Regency. Meanwhile, the number of respondent samples that have been determined in this study is 100 people.The results showed that location and service quality had a positive and significant effect on customer loyalty of BRILink Kembar Sepasang Dusun II Penarik Muko-Muko Regency, both partially and simultaneously. So, it can be concluded that the more strategic the location and the good quality of service felt by customers who use financial services at BRILink Kembar Sepasang Agents, the greater the level of loyalty created.